Hubungan Self Control dengan Perilaku Academic Cheating dalam Sistem Pembelajaran Berbasis Digital pada Siswa - Dwi Rezki Wahyuni; Eva Meizara Puspita Dewi; Andi Halimah (SEMINAR NASIONAL DIES NATALIS 62, 2023)
Students who have low self-control abilities in undergoing digital-based learning processes will make it easier for students to abuse opportunities and become one of the causes of academic cheating behavior. This study aims to determine the relationship between self-control and academic cheating behavior in a digital-based learning system for students at SMPN 13 Sinjai. The method used in this study is a quantitative method involving 132 respondents who are students of SMPN 13 Sinjai. The measuring instrument in this study uses a self-control scale and an academic cheating scale. The data analysis technique used in this research is the product moment correlation which is processed using the SPSS 24.00 for windows program. The results of this study indicate that there is a relationship between self-control and academic cheating behavior in digital-based learning systems for students of SMPN 13 Sinjai (p=0.039 & r=-1.80). This means that there is a negative relationship between self-control and academic cheating behavior in digital-based learning systems for students at SMPN 13 Sinjai. The results of this study are expected to be a reminder for students to be able to improve their self-control abilities in the digital learning era and suppress academic cheating behavior.